HUBUNGAN ANTARA KOMPETENSI GURU DAN DISIPLIN GURU TERHADAP PRESTASI BELAJAR SISWA KELAS XII DI SMK YADIKA 3 JAKARTA - Gordon Aruan; Agus Wahyono (Pasca Sarjana Universitas Satya Negara Indonesia, 2015)
This study examined the correlation between competence and discipline of teachers with the performance students 1grade 3 in SMK Yadika 3 Jakarta. This research was intended to: (a) analyze the effects of teachers competence on students’ performances, (b) analyze the effects of teachers discipline on students’ performances and (c) analyze the combined effects of competence and discipline of teachers 2 on students’ performances. The data were collected from SMK Yadika 3 Jakarta Jalan Kamal Raya No. 42 Tegal Alur Kecamatan Kalideres Jakarta Barat start from May until September 2013 with analysed using correlation. A total of 72 employees from 246 participated in this study. It’s using likert scale for measurement. Data collected by using thesimple random sampling technique which’s there only 4 class. Data was analyzed with correlation and regression. The findings again showed that competence and disilpline teachers have positive and significant link with performances students.